Os sentidos do trabalho para profissionais da saúde do CTI de um hospital universitário - Carolina da Silva Caram (2013)
The People give life and dynamic to organization, the subjectivity of people moving the work and relationships inherent in to it. In health the work differs from the others, especially regarding to interpersonal relations and subjectivity of workers and customers. The Intensive Care Unit which operate in different categories of professionals in providing intensive care to patients in critical health conditions, have a unique way of life that makes the professionals attributing meaning of work differently. For the service provided is consistent with both the organization and the principles and values of the professional is necessary for workers to attribute meaning of work. The term meaning refers to the understanding of the rationale to be of the professionals to do their jobs. Given the above, this study aimed to understand the meanings of work for health professionals who work in the ICU of a university hospital in Belo Horizonte. This is a qualitative study conducted in an Intensive Care Unit of a university hospital in Belo Horizonte, Minas Gerais. The subjects were 31 health professionals who worked in direct patient care in the Intensive Care Unit, namely: nurses, nursing technicians, doctors, physiotherapists, speech therapists, nutritionists and psychologists. Data was collected through interviews with semi-structured analyzed by content analysis of Bardin. We analyzed four dimensions of meaning of work: the individual dimension, organizational, social and daily activities. The individual dimension is related to the professional aspects of the subjects that have significant proportions in personal life. The individual values the professional recognition they receive from others and yourself. Also, realize that through the labor he is able to grow personally and professionally in addition to satisfy. The organizational dimension associated with the identification of the professional organization . Thus, it was observed that dimension organizational structure, teamwork, interpersonal relationships and the role of these in the social life of the professional, organizational commitment and recognition of the institution. The dimension to everyday professional work focuses on the act, do work and those resulting from the same, as the pleasure in seeing your work and patient recovery, the perception of the effectiveness and usefulness of it. The social dimension analyzes the social value of work as well as his contribution and inclusion in society. The meaning of work for health professionals working in an ICU in which they act different categorical professionals articulate and reframe the work becomes relevant in the organization of the work process and managerial practices. Moreover, can contribute to design ways to revalue the work and give direction to act in line with organizational goals avoiding deviations of behaviors that endanger the assistance beyond the redemption of the human being in its subjective dimension in health practices.